Mobilizing European law. Issue 9 (2nd September 2018) - Conant, Lisa; Hofmann, Andreas; Soennecken, Dagmar; Vanhala, Lisa
ABSTRACT: The literature on European legal mobilization asks why individuals, groups and companies go to court and explores the impact of litigation on policy, institutions and the balance of power among actors. Surveying the literature we find that legal mobilization efforts vary across policy areas and jurisdictions. This article introduces a three-level theoretical framework that organizes research on the causes of these variations: macro-level systemic factors that originate in Europe; meso-level factors that vary nationally; and micro-level factors that characterize the actors engaged in (or disengaged from) litigation. We argue that until we understand more about how and why different parties mobilize law, it is difficult to respond to normative questions about whether European legal mobilization is a positive or negative development for democracy and rights.